2022
DOI: 10.3390/cells12010022
|View full text |Cite
|
Sign up to set email alerts
|

Current Therapeutic Options and Potential of Mesenchymal Stem Cell Therapy for Alcoholic Liver Disease

Abstract: Alcoholic liver disease (ALD) is a globally prevalent chronic liver disease caused by chronic or binge consumption of alcohol. The therapeutic efficiency of current therapies for ALD is limited, and there is no FDA-approved therapy for ALD at present. Various strategies targeting pathogenic events in the progression of ALD are being investigated in preclinical and clinical trials. Recently, mesenchymal stem cells (MSCs) have emerged as a promising candidate for ALD treatment and have been tested in several cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 223 publications
0
5
0
Order By: Relevance
“…Since the liver is the main barrier to toxic substances in the body, the main metabolism of ethanol occurs in it during alcohol intoxication. The metabolism of ethanol in the liver leads to formation of various hepatotoxic by-products and significant oxidative stress in the liver, and, as a result, to the death of hepatocytes [21].…”
Section: Resultsmentioning
confidence: 99%
“…Since the liver is the main barrier to toxic substances in the body, the main metabolism of ethanol occurs in it during alcohol intoxication. The metabolism of ethanol in the liver leads to formation of various hepatotoxic by-products and significant oxidative stress in the liver, and, as a result, to the death of hepatocytes [21].…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating studies demonstrated that a pivotal issue relates to the identification of those factors that trigger inflammation, thus fuelling the transition from NAFLD to NASH ( Guo et al, 2022 ; An et al, 2023 ). These triggers of inflammtion in liver might be associated with their origins outside the liver as well as inside the organ, both of which accelerate to NASH development ( Han et al, 2022 ). Although the marked progress in unravelling the mechanism that underlie NAFLD development and progression has made, yet the elucidation of its mechanism about the pathogenesis remains limited.…”
Section: Extrahepatic Factors In Nashmentioning
confidence: 99%
“…Extensive evidence has demonstrated that MSC-based therapy for liver cirrhosis primarily targets anti-inflammatory and anti-fibrotic effects, as well as promoting liver repair through paracrine cytokines, immune regulation, and facilitation of extracellular matrix degradation via various signaling pathways, such as TGF-β1/SMAD, Wnt/β-catenin, Ras/ERK, or Notch [ [13] , [14] , [15] , [16] , [17] , [18] ]. Presently, the transplantation of MSCs for the treatment of liver cirrhosis has been registered and its therapeutic effect has been verified in numerous clinical trials [ [19] , [20] , [21] ]. However, the main method of MSCs transplantation, peripheral intravenous injection, results in approximately 80 % of MSCs being distributed in the lungs.…”
Section: Introductionmentioning
confidence: 99%